BIG DATA WORLD AND THE NEW MARKETING HORIZONS (Revista Inclusiones, 2021)
Marketing has undergone major transformations in the last two decades. Today, people spend mostof their time on the Internet. Big data has changed the business landscape beyond recognition, andthe marketing industry has been hit hardest by these changes. Technological changes give a widefield for entrepreneurs to operate with ease with a huge amount of data and to make adequatelyinformed decisions. Large information flows allow easier interpretation of consumer behaviour, whichopens opportunities to understand better customer needs and the maximum adaptation of productdecisions to their requirements. The technological environment has created conditions for marketersto reach their potential. Today, more than ever, highly targeted messages can be sent to the rightaudience. Customer service is a priority for companies, and this puts companies to the test forsystematic market monitoring and adaptation to new technological solutions. The digital age gives anequal start to all companies. Marketers are well aware of the benefits that the digital environmentoffers, because today, it is not important how big you are in business, but how fast and adaptable tochange. The article's main goal is to present how the digital transformation affects the marketingindustry, presenting the benefits provided by the digital environment for business developmentthrough the application of innovative marketing solutions for successful positioning. The main aspectsof big data and their influence in the marketing industry are systematized. The main research methodsin the development are content analysis, the method of analysis and synthesis and the intuitive andsystematic approach.